Associations Between Physician Prescribing Behavior and Persistent Postoperative Opioid Use Among Cancer Patients Undergoing Curative-intent Surgery: A Population-based Cohort Study. Issue 2 (February 2022) - Xu, Yuan; Cuthbert, Colleen A.; Karim, Safiya; Kong, Shiying; Dort, Joseph C.; Quan, May Lynn; Hinther, Ashley V.; Quan, Hude; Hemmelgarn, Brenda R.; Cheung, Winson Y.
Abstract : Objective: This study aimed to evaluate the association between prescribers' opioid prescribing history and persistent postoperative opioid use in cancer patients undergoing curative-intent surgery. Background: Study has shown that patients may be over-prescribed analgesics after surgery. However, whether and how the prescriber's opioid prescribing behavior impacts persistent opioid use is unclear. Methods: All adults with a diagnosis of solid cancers who underwent surgery during the study period (2009–2015) in Alberta, Canada and were opioid-naïve were included. The key exposure was the historical opioid-prescribing pattern of a patient's most responsible prescriber. The primary outcome was "new persistent postoperative opioid user, " was defined as a patient who was opioid-naïve before surgery and subsequently filled at least 1 opioid prescription between 60 and 180 days after surgery. Results: We identified 24, 500 patients. Of these, 2106 (8.6%) patients became a new persistent opioid user after surgery. Multivariate analysis demonstrated that patients with most responsible prescribers that historically prescribed higher daily doses of opioids (≥50 vs <50 mg oral morphine equivalent) had an increased risk of new persistent opioid use after surgery (odds ratio = 2.41, P < 0.0001). In addition to the provider's prescribing pattern, other factors including younger age, comorbidities, presurgical opioid use, chemotherapy, type of tumor/surgical procedure were also found to be independently associated with new persistent postoperative opioid use. Conclusions: Our results suggest that prescriber with a history of prescribing a higher opioid dose is an important predictor of persistent postoperative opioid use among cancer patients undergoing curative-intent surgery. Abstract : Supplemental Digital Content is available in the text